2019
DOI: 10.1101/gr.244780.118
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-independent molecular actions of mutant estrogen receptor 1 in endometrial cancer

Abstract: Estrogen receptor 1 (ESR1) mutations have been identified in hormone therapy-resistant breast cancer and primary endometrial cancer. Analyses in breast cancer suggest that mutant ESR1 exhibits estrogen-independent activity. In endometrial cancer, ESR1 mutations are associated with worse outcomes and less obesity, however, experimental investigation of these mutations has not been performed. Using a unique CRISPR/Cas9 strategy, we introduced the D538G mutation, a common endometrial cancer mutation that alters t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 43 publications
(88 reference statements)
5
47
2
Order By: Relevance
“…Mutant clones were generated using the CETCH-seq method described by Savic et al (21). We followed procedures outlined by Blanchard et al (22) (Supplemental Fig. S1a) using the same guide RNA/Cas9 vector and WT and D538G pFETCH vectors for mutant and WT ER clone generation.…”
Section: Generation Of Mutant Clonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant clones were generated using the CETCH-seq method described by Savic et al (21). We followed procedures outlined by Blanchard et al (22) (Supplemental Fig. S1a) using the same guide RNA/Cas9 vector and WT and D538G pFETCH vectors for mutant and WT ER clone generation.…”
Section: Generation Of Mutant Clonesmentioning
confidence: 99%
“…72 hours post-transfection, cells were treated with G418 (Thermo Fisher Scientific) at 300ug/ml final concentration, which was applied every two days in conjunction with media changes. Single-cell clones were picked and validated using the same procedures as described by Blanchard et al (22) including limiting dilution plating, colony picking, sanger sequencing and FLAG and ER immunoblots. In all, two clones for each genotype (WT, Y537S, and D538G) were validated for both T-47D and MCF-7 cell lines.…”
Section: Generation Of Mutant Clonesmentioning
confidence: 99%
“…Mutant clones were generated using the CETCH-seq method described by Savic et al (36). We followed procedures outlined by Blanchard et al (22) (Supplemental Fig. S1a) using the same guide RNA/Cas9 vector and WT and D538G pFETCH vectors for mutant and WT ER clone generation.…”
Section: Generation Of Mutant Clonesmentioning
confidence: 99%
“…Beyond breast cancer, three potentially-pathogenic ESR1 mutations were very recently identified in cervical squamous cell carcinoma samples [ 48 ]; thus, it would be interesting to use this highly sensitive and specific methodology in cervical cancer samples and potentially pre-malignant cases of endometriosis as well. Very recently, a de Novo ESR1 Hotspot Mutation was detected in a patient with endometrial cancer treated with an aromatase inhibitor [ 49 ], while it has been reported that—in endometrial cancer— ESR1 mutations are associated with worse outcomes and less obesity [ 50 ]. However, the experimental investigation of ESR1 mutations in endometrial cancer has not been performed.…”
Section: Discussionmentioning
confidence: 99%